The impact of shift starting time on sleep duration, sleep quality, and alertness prior to injury in the People's Republic of China. (December 2014) - Lombardi, David A.; Jin, Kezhi; Vetter, Céline; Courtney, Theodore K.; Folkard, Simon; Arlinghaus, Anna; Liang, Youxin; Perry, Melissa J.
<x xml:space="preserve">Abstract</x> Early shift start time and night shifts are associated with reduced sleep duration and poor sleep quality that often lead to increased fatigue levels, performance decrements and adverse safety and health outcomes. This study investigates the impact of shift starting time on sleep patterns, including the duration and quality of sleep and alertness/sleepiness at the time of injury, in a large epidemiological field study of hospitalized adults with severe work-related hand injury in the People's Republic of China (PRC) from multiple industries with severe work-related traumatic hand injury were recruited from 11 hospitals in three industrially-developed cities in the PRC: Ningbo, Liuzhou and Wuxi. Analysis of covariance (ANCOVA) was used to compare sleep duration, sleep quality and alertness/sleepiness across 3 h increments of shift start time, while adjusting for age, gender, work hours, shift duration, day of injury and several transient work-related factors. Effect modification by gender was also evaluated. Seven-hundred and three hospitalized adults (96.4%) completed a face-to-face interview within 4 days of injury; 527 (75.0%) were male, with a mean (±SEM) age of 31.8 ± 0.4 years. Overall, these adults worked relatively long weekly (55.7 ± 0.6 h) and daily hours (8.6 ± 0.07 h). Average sleep duration prior to injury was 8.5 h (±0.07), and showed significant variations (p value <0.05) across shift starting time increments. Overall mean prior sleep duration was shortest for individuals starting shifts from "21:00–23:59" (5.6±0.8 h) followed by midnight "00:00–02:59" (6.1 ± 0.6 h). However, a statistically significant interaction (p < 0.05) was observed between gender and shift starting time on mean sleep duration. For males the shortest sleep duration was 5.6 h ("21:00–23:59") and for females the shortest was 4.3 h ("24:00–02:59" and "15:00–17:59"). Sleep quality (generally quite well) and alertness/sleepiness based on the KSS (generally alert) did not vary significantly across shift starting time. Results suggest that sleep duration is shortest among injured PRC adults starting shifts late night and early morning. However, with more than 8.5 h of sleep on average work days, Chinese slept much longer than typical US day workers (Sleep in America Poll, 2012, 6:44 on workdays, 7:35 on free days), and this may help to explain higher than expected alertness/sleepiness scores at the time of injury.